2014
DOI: 10.1007/s00339-014-8610-1
|View full text |Cite
|
Sign up to set email alerts
|

A simple strategy to fabricate poly (acrylamide-co-alginate)/gold nanocomposites for inactivation of bacteria

Abstract: A facile and efficient approach to prepare uniform gold nanoparticles (Au NPs) in hybrid hydrogel consisting of acrylamide (AM) and alginate (SA) for antibacterial applications is reported. In this study, reduction of gold ions by acrylamide and alginate (AM-SA) occurred before the polymerization and as-obtained gold colloids are stabilized by AM-SA immediately in the absence of commonly used reducing agents and protective reagents. Via transmittance electron microscopy results, we can conclude that the obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Carbohydrate functionalization/stabilization of AuNPs makes them multivalent systems, thus facilitating their interactions with proteins like lectins . There are different pathways to produce poly­(acrylamide) composites with AuNPs (i) by polymerizing acrylamide along with a cross-linker and then synthesizing AuNPs or (ii) by reacting HAuCl 4 with poly­(acrylamide) under basic pH. , However, the synthesis of nanocomposites through the latter pathway is the least explored. Incidentally, Tatarchuka et al reported the reaction of HAuCl 4 with acrylamide in water to yield a colloidal solution of AuNPs, stable for few days …”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate functionalization/stabilization of AuNPs makes them multivalent systems, thus facilitating their interactions with proteins like lectins . There are different pathways to produce poly­(acrylamide) composites with AuNPs (i) by polymerizing acrylamide along with a cross-linker and then synthesizing AuNPs or (ii) by reacting HAuCl 4 with poly­(acrylamide) under basic pH. , However, the synthesis of nanocomposites through the latter pathway is the least explored. Incidentally, Tatarchuka et al reported the reaction of HAuCl 4 with acrylamide in water to yield a colloidal solution of AuNPs, stable for few days …”
Section: Introductionmentioning
confidence: 99%